(untitled) (Altre Modernità, 2020)
This paper takes shape from the debate on the role of human rights in maternity care, following several emerging cases of obstetric violence and aggressive and intolerant treatment permeating care during labour and delivery (Freedman et al.). In 2015, the WHO released a statement to prevent and eliminate disrespectful, nondignified behaviour by health professionals during childbirth, highlighting a physical as well as emotional and psychological violence. Early in 2019, a UN report warned against obstetric violence as being still widespread and systematic in nature, acknowledging it has not been fully addressed from a human rights perspective so far. Despite the fact that the phenomenon is gaining recognition worldwide, there seems to be a lack of theoretical engagement on the issue (Dixon). This study, therefore, explores how women’s experiences are discursively construed, taking into account the stories shared on social media—in advocacy websites, blogs, Facebook groups, and a series of relevant hashtag threads. Indeed, social media are being used by patients as a platform for exchanging their views, writing their testimonies, thus creating a (safe) site for the production of meanings (Baumann). While projecting the image of suffering bodies facing abuse, humiliation and unconsented medical procedures, these narratives allow a critical thought on practices of discrimination which heavily affect women’s agency and act like a prism reflecting dominant dynamics in society.